Quality and Readability Assessment of Patient-Centered Online Information on Apical Surgery - Pablo Álvarez-Nóvoa; Ramón Miguéns-Vila; Benjamín Martín-Biedma; Gustavo De-Deus; María Pilar Pecci-Lloret; Miriam Teulé-Trull; Juan Seoane-Romero; Pablo Castelo-Baz (International Dental Journal)
Introduction and aims: Nowadays, patients seek medical information online. Patient-oriented content must be easy to read and trustworthy. This study aimed to assess the quality and readability of online information about apical surgery and apicoectomy in English and Spanish. Methods: The authors performed the following systematic searches on Google in February 2023: “apicoectomy”, “apicectomía”, “apical surgery”, and “cirugía apical”. The first 100 websites of each query were selected. English readability was assessed using Flesch-Kincaid Reading Grade Level, Flesch Reading Ease Score, Gunning Fog Index, Coleman-Liau Index, Automated Readability Index and Simple Measure of Gobbledygook Index. The Fernández-Huerta Index and INFLESZ were used to assess Spanish readability. Quality was measured using the DISCERN tool. Results: A total of 165 sites were included in total. Readability for English-language sites (“apical surgery” and “apicoectomy”) was categorised as “fairly difficult to read” [FRES (apical surgery) = 54.7; FRES (apicoectomy) = 54.3]. Similarly, Spanish sites (“cirugía apical” and “apicectomía”) were classified as “relatively difficult to read”. Overall, the DISCERN tool showed a low average quality of information for all terms analysed. Conclusion: English and Spanish online information about apical surgery is difficult for the average patient to understand and presents significant quality deficiencies. Clinical relevance: The Internet is a powerful tool for communicating with patients, but available apical surgery information is difficult for laypersons to understand and has a low overall quality. To overcome this issue, endodontists should produce high-quality, patient-relevant materials in plain language.